Land Use Change and Soil Comparison between 1983 and 2023 in the Municipality of Jiutepec, Morelos, Mexico (TERRA LATINOAMERICANA, 2026)
The modifications in land use and vegetation resulting from human activities are evident at both local and global scales. The primary consequences include biodiversity loss and a decline in the quality and quantity of ecosystem services. In this context, anthropogenic activities such as agriculture negatively impact ecosystems and their components, with soil being one of the most af fected resources. Therefore, a detailed study of the dynamics of these modifications constitutes a valuable tool for land management, enabling the identification of specific areas where conservation and restoration strategies can be developed. The objective of this study was to assess land use and vegetation change dynamics over a 27-year period, as well as variations in soil properties over a 40-year period in the municipality of Jiutepec, Morelos. Geographic Information Systems were used to generate vector data on land use and vegetation for the years 1995 and 2022. A simplified change matrix was constructed, and the change rate and deforestation rate were calculated. A total of 16 land use categories were identified for 1995 and 17 for 2022. The most significant changes in Jiutepec included an increase in urban areas of approximately 1136.27 ha. Regarding the deforestation rate, the most af fected categories were conserved and disturbed tropical dry forest. In the determination of soil properties, some properties currently evaluated (2023) remain within the ranges reported in the past (1983).
Keywords: soil quality; vegetation cover; deforestation; urban area